The Effect of Profitability and Leverage on Tax Avoidance with Good Corporate Governance as a Mediating Variable - Marcelino Andrew Wijaya; Rino Tam Cahyadi; Lalu Rahmat Sohdi; Bagas Brian Pratama (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the effect of profitability, leverage, and good corporate governance on tax avoidance , as well as to examine the role of good corporate governance as a mediating variable in the relationship between profitability and leverage on tax avoidance in Food and Beverage subsector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses a quantitative approach with secondary data obtained from the companies' annual financial reports. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression analysis, path analysis , and the Sobel test. The results show that profitability has no significant effect on tax avoidance. Leverage has a negative and significant effect on tax avoidance, while good corporate governance also has a negative and significant effect on tax avoidance. The mediation test shows that good corporate governance is unable to mediate the effect of profitability on tax avoidance, but is able to mediate the effect of leverage on tax avoidance. The results of this study indicate that tax avoidance practices in Food and Beverage subsector companies are more influenced by the company's funding structure and the effectiveness of corporate governance mechanisms than by the company's level of profitability.